Crystal structure of MboIIA methyltransferase - Osipiuk, Jerzy (Oxford University Press, 2003)
DNA methyltransferases (MTases) are sequence-specific enzymes which transfer a methyl group from S-adenosyl-l-methionine (AdoMet) to the amino group of either cytosine or adenine within a recognized DNA sequence. Methylation of a base in a specific DNA sequence protects DNA from nucleolytic cleavage by restriction enzymes recognizing the same DNA sequence. We have determined at 1.74 Å resolution the crystal structure of a β-class DNA MTase MboIIA (M·MboIIA) from the bacterium Moraxella bovis, the smallest DNA MTase determined to date. M·MboIIA methylates the 3′ adenine of the pentanucleotide sequence 5′-GAAGA-3′. The protein crystallizes with two molecules in the asymmetric unit which we propose to resemble the dimer when M·MboIIA is not bound to DNA. The overall structure of the enzyme closely resembles that of M·RsrI. However, the cofactor-binding pocket in M·MboIIA forms a closed structure which is in contrast to the open-form structures of other known MTases.